Non-uniform interaction effect of flow and rigid submerged vegetation on turbulent flow characteristics - Mohammad Hadi Fattahi; Mohammadhadi mohammadi; Amin Rostami Ravari (مهندسی منابع آب)
The shear instability causes the exchange of mass and momentum between the inner and upper layers of the vegetation. The experiments of this research were carried out in a straight rectangular channel with a length of 14 meters, a width of 90 cm and a depth of 60 cm under a constant flow rate of 31.7 liters per second. A three-dimensional sandy well with a submerged rigid plant flow slope with a height of 12 cm and a diameter of 10 cm with a constant surface density of 0.004 on a decelerating 10.75 degree and an accelerating flow slope of 7.96 degrees was constructed with a sand bed and shaped elements. The substrate is irregularly distributed. The findings of the research showed that the maximum flow speed occurred at y/h=0.52 for the decelerating flow and at y/h=0.47 for the accelerating flow. Therefore, it seems that the validity depth of the logarithmic law was a function of the measurement position of the velocity profile and the non-uniform distribution of submerged solid plant elements on the three-dimensional shape of the sandy well bed. Examining the speed reduction law has indicated that the Kells rise function in the decelerating and accelerating flow sections in the test conditions have values ​​of Π=-2.8 and Π=-5. In any case, sections of decelerating and accelerating currents in a three-dimensional sand pit in the presence of submerged rigid plant elements can act as an obstacle in the flow and cause the water to bend and rotate around them.